PENGARUH BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK IPHONE - dio faidalen; Yenny Yuniarti (DIGEST MARKETING, 2018)
The study purpose is to determine whether brand awareness, brand association, quality perceptions, and brand loyalty has a positive influence on the iPhone purchase decision both simultaneously and partially. Sample consists of 100 respondents. The type of research used is explanatory research (explanatory research) and hypothesis testing itself using used multiple linear regression procedure. The results showed that the influence either simultaneously or partially is significantly positive. As luxuries appliance, IPhone should appeal the customers to make customer move from repetitive purchasing to be loyal.